13 Opportunities for using low-protein diets for weanling pigs to improve intestinal health - Nyachoti, Martin (J Anim Sci, 2020)
Dietary manipulation with respect to crude protein (CP) content has been suggested as part of the overall strategy for the nutritional management of weanling pigs to improve intestinal health. This has focused on the use of low CP diets that are appropriately fortified with crystalline amino acids (AA). Use of low CP diets minimizes the amount of undigested dietary protein entering the large intestine and being subjected to bacterial fermentation. This is important because protein fermentation leads to the production of toxic metabolites and encourages the proliferation of pathogenic bacteria, thus causing enteric problems such as post-weaning diarrhea. There have been considerable efforts to elucidate the mechanisms underlying the potential benefits of feeding low CP diets to piglets. In addition to impacting the intestinal microbiome and its associated activities, it is clear that feeding a low CP diets interferes with the attachment of enterotoxigenic E. coli to the intestinal mucosa, thus minimizing its ability to cause disease. Another area of interest has been how use low CP diets in combination with other dietary manipulations to further enhance intestinal health in piglets. In this regards, existing evidence suggests that a low CP diet may be used in combination with other dietary interventions, such as probiotics and dietary fiber, to further enhance gut health outcomes in piglets. Also, addressing the potential reduction in piglet performance when feeding low CP diets by looking more into diet formulation to avoid deficiencies of essential AA or even some of non-essential AA, is critical for successful use low CP diets. Based on the available information, a reduction of dietary protein by four percentage units coupled with appropriate AA supplementation can be a useful dietary strategy to improve intestinal health.